Case Report: Coexistence of Anti-Glomerular Basement Membrane Disease, Membranous Nephropathy, and IgA Nephropathy in a Female PatientWith Preserved Renal Function - Qu, Wei; Liu, Nan; Xu, Tianhua; Tian, Binyao; Wang, Meng; Li, Yanqiu; Ma, Jianfei; Yao, Li (Frontiers in Pharmacology, 2022)
Coexistence of anti-glomerular basement membrane (GBM) disease, idiopathic membranous nephropathy (IMN), and IgA nephropathy in one patient is a very rare case, which has not yet been reported. Whether the three diseases are correlated and the underlying mechanism remain unknown. Here we report a 48-year-old female patient that was admitted because of proteinuria and abnormal renal function, which was diagnosed as anti-GBM disease, IMN, and IgA nephropathy by renal biopsy. The patient received treatment including high-dose methylprednisolone pulse therapy, plasma exchange, and intravenous infusion of both cyclophosphamide (CTX) and rituximab. In the follow-up, the titer of the anti-GBM antibody gradually decreased, renal function was restored, and urinary protein reduced, without significant adverse effects.